2016
DOI: 10.1093/treephys/tpw117
|View full text |Cite
|
Sign up to set email alerts
|

Thermotolerance and heat stress responses of Douglas-fir and ponderosa pine seedling populations from contrasting climates

Abstract: Temperature and the frequency and intensity of heat waves are predicted to increase throughout the 21st century. Germinant seedlings are expected to be particularly vulnerable to heat stress because they are in the boundary layer close to the soil surface where intense heating occurs in open habitats. We quantified leaf thermotolerance and whole-plant physiological responses to heat stress in first-year germinant seedlings in two populations each of Pinus ponderosa P. and C. Lawson (PIPO) and Pseudotsuga menzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 74 publications
4
42
0
1
Order By: Relevance
“…Differences between the sensitivity of ponderosa pine and Douglas‐fir juveniles to climate are consistent with findings showing greater shade and heat tolerance in Douglas‐fir than ponderosa pine seedlings (Marias et al. ), although the same differences in sensitivity were not apparent for adult growth. Despite potential species‐specific responses to future climate change, the overall sensitivity of adult and juvenile growth to water availability and increasing temperatures suggests that future climatic changes will cause overall declines in tree growth at and near lower treeline.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Differences between the sensitivity of ponderosa pine and Douglas‐fir juveniles to climate are consistent with findings showing greater shade and heat tolerance in Douglas‐fir than ponderosa pine seedlings (Marias et al. ), although the same differences in sensitivity were not apparent for adult growth. Despite potential species‐specific responses to future climate change, the overall sensitivity of adult and juvenile growth to water availability and increasing temperatures suggests that future climatic changes will cause overall declines in tree growth at and near lower treeline.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, higher sensitivity of juvenile ponderosa pine growth to water deficit and maximum temperature in recent decades, relative to Douglas-fir, suggests that future increases in temperature and water deficit may affect ponderosa pine juveniles more so than Douglas-fir juveniles. Differences between the sensitivity of ponderosa pine and Douglas-fir juveniles to climate are consistent with findings showing greater shade and heat tolerance in Douglas-fir than ponderosa pine seedlings (Marias et al 2017), although the same differences in sensitivity were not apparent for adult growth. Despite potential species-specific responses to future climate change, the overall sensitivity of adult and juvenile growth to water availability and increasing temperatures suggests that future climatic changes will cause overall declines in tree growth at and near lower treeline.…”
Section: Implications Of Future Climate Changesupporting
confidence: 86%
“…Provenance, greenhouse, and common garden studies have been used to examine how the differential expression of functional traits in seedling populations and families from contrasting climates influences physiological responses to drought. Populations and families from drier climates often exhibit functional traits that enable them to enhance water and nutrient uptake and resist drought more effectively than populations and families from wetter climates (Fernández et al, 1999;Cregg and Zhang, 2001;Nguyen-Queyrens and Bouchet-Lannat, 2003;Gratani, 2014;Kerr et al, 2015;Carvalho et al, 2017;Marias et al, 2017;Moran et al, 2017). Drought resistance is defined as the capacity of plants to avoid or tolerate drought, which is achieved through diverse physiological mechanisms (Levitt, 1980;Khanna-Chopra and Singh, 2015;Polle et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to seedling populations and families from wetter climates, seedling populations and families from drier climates can exhibit increased resource allocation to root growth which enhances water and nutrient uptake. Seedling populations and families from drier climates also can exhibit greater leaf carbon isotope ratios which indicate greater intrinsic water use efficiency and greater stomatal constraints on gas exchange, and lower leaf turgor loss point which can indicate greater drought tolerance (Grossnickle et al, 1996;Cregg and Zhang, 2001;Nguyen-Queyrens and Bouchet-Lannat, 2003;López et al, 2009;Bartlett et al, 2014;Kerr et al, 2015;Carvalho et al, 2017;Marias et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, such inhibition of photosynthesis can not only arise from exposure to high light in the absence of other stresses, but also from too much light in the presence of other stresses that limit photosynthesis and thus, plant growth [14]. Studies on extreme temperatures suggested that heat stress significantly inhibited the maximal (F v /F m ) and effective quantum yield of PSII photochemistry (Φ PSII ), and decreased the relative leaf chlorophyll content [15][16][17]. When facing low temperature stress, however, plants showed a sustained NPQ and improved photo-protection, which is associated with the reorganization of the light harvesting complex into aggregates [18,19].…”
Section: Introductionmentioning
confidence: 99%